Ultrasound-Guided Popliteal Nerve Block in a Patient with Malignant Degeneration of Neurofibromatosis 1 - Arjun Desai; Brendan Carvalho; Jenna Hansen; Jonay Hill (Case Reports in Anesthesiology)
A 41-year-old female patient with neurofibromatosis 1 presented with new neurologic deficits secondary to malignant degeneration of a tibial lesion. Ultrasound mapping of the popliteal nerve revealed changes consistent with an intraneural neurofibroma. Successful popliteal nerve blockade was achieved under ultrasound guidance.